1997
DOI: 10.1099/00207713-47-4-1249
|View full text |Cite
|
Sign up to set email alerts
|

Proposal To Reclassify Zoogloea ramigera IAM 12670 (P. R. Dugan 115) as Duganella zoogloeoides gen. nov., sp. nov.

Abstract: The taxonomic position of a misclassified strain, Zoogloea ramigera IAM 12670T (= ATCC 25925T = P. R. Dugan lUT), was reevaluated. A phylogenetic analysis based on 16s ribosomal rDNA sequences revealed that this organism was located in the beta subclass of the class Proteobacteria with members of the genus TeZZuria as its closest relatives. On the basis of phenotypic and phylogenetic information, we propose that this organism should be reclassified in a new taxon with the name Duganella zoogloeoides gen. nov.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 18 publications
3
53
1
Order By: Relevance
“…which has recently been reclassified as a new taxon with the name Duganella zoogloeoides (Hiraishi et al, 1997). The cells of these known species themselves are not small as described in literature (Doudroff and Palleronii, 1974;Hiraishi et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…which has recently been reclassified as a new taxon with the name Duganella zoogloeoides (Hiraishi et al, 1997). The cells of these known species themselves are not small as described in literature (Doudroff and Palleronii, 1974;Hiraishi et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Crabtree I-16-M) was reclassified in a new genus of Rhizobiales and renamed Shinella zoogloeoides, while another suggested neotype strain Z. ramigera ATCC 25925 (¼P.R. Dugan 115 strain) was renamed as Duganella zoogloeoides of Burkholderiales based on 16S rRNA gene sequence analysis (Hiraishi et al, 1997). Three oligonucleotide probes complementary to the 16S rRNAs of Z. ramigera ATCC 19544 were designed to detect the bacterial cells that accumulated in the typical branched gelatinous matrices, the so-called Zoogloea fingers (Wagner et al, 1993;Rossello-Mora et al, 1995) and it was shown that Zoogloea cells accounted for up to approximately 10% of the total cell numbers.…”
Section: Introductionmentioning
confidence: 99%
“…n. Naxi referring to the Naxi nationality, who lived in Lijiang, Yunnan Province, China, from where the organism was isolated; n. bacter from Table 1. Phenotypic properties separating strain YIM 31775 T from related taxa Taxa: 1, Massilia; 2, Duganella zoogloeoides; 3, Janthinobacterium; 4, Telluria; 5, YIM 31775 T (data from this study and Lincoln et al, 1999;Bowman et al, 1993;La Scola et al, 1998;Lindquist et al, 2003;Hiraishi et al, 1997). +, Positive; (+), weakly positive; 2, negative; V, variable among species or strains; polar (m), polar monotrichous; ND, no data.…”
mentioning
confidence: 99%